2003
DOI: 10.1007/s00467-003-1147-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment data during pediatric home peritoneal teledialysis

Abstract: Peritoneal teledialysis (telePD) is a modembased communication link between the patients' cyclers and a computer in the dialysis unit that allows the transmission and storage of a series of automated peritoneal dialysis (APD) treatment data. In order to evaluate the usefulness of telePD in quantifying the problems that may occur during pediatric APD, we retrospectively studied four patients with a median age of 14.1±1.8 years during their initial months of telePD. The selection criteria were potential non-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…Of the few studies in the literature exploring the use of RM for PD, most report findings similar to ours [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. For instance, Gallar et al [ 15 ] reported reduced clinical examination time for PD patients using home videoconferencing equipment compared with hospital consultation (22 vs. 33 minutes, p < 0.05), and reduced hospitalization rates (2.2 vs. 5.7 days/patient/year, p < 0.05).…”
Section: Discussionsupporting
confidence: 80%
“…Of the few studies in the literature exploring the use of RM for PD, most report findings similar to ours [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. For instance, Gallar et al [ 15 ] reported reduced clinical examination time for PD patients using home videoconferencing equipment compared with hospital consultation (22 vs. 33 minutes, p < 0.05), and reduced hospitalization rates (2.2 vs. 5.7 days/patient/year, p < 0.05).…”
Section: Discussionsupporting
confidence: 80%
“…At present, several small observational studies on RPM in dialysis patients suggest the technical feasibility and numerous potential benefits of RPM. 18 , 25 , 26 , 27 , 28 However, many potential opportunities identified by the consensus panel have yet to be explored ( Figure 1 ).
Figure 1 Opportunities for remote patient management.
…”
Section: Methodsmentioning
confidence: 99%
“…Many of these benefits, although intuitive, are currently hypothetic and few clinical studies (Table 2 lists clinical studies in this area) have demonstrated specific benefits of telehealth services for patients with ESRD. The current literature in this are single center experiences utilizing telemedicine for the care of patients receiving HD (14-23) or PD (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Thus, studies that address the utility of telehealth and include endpoints of interest to patients, providers, and payers (i.e., improvements in mortality, lowering of readmission rates, improved quality of life, and cost savings) are needed.…”
Section: Opportunities For the Care Of Patients With Esrdmentioning
confidence: 99%
“…Through the provision of a suite of telehealth services, patient satisfaction may increase with home therapies. Although small studies support the idea that patient satisfaction with telemedicine care for patients with ESRD will be high, further studies are needed in this domain (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). There are potential downsides to telemedicine in terms of perceived intrusion into privacy and depersonalization that will also need to be investigated.…”
Section: Improved Patient Satisfactionmentioning
confidence: 99%